Prevalence and risk factors of early postoperative seizures in patients with glioma: a systematic review and meta-analysis - Sun, Bo; Sun, Yuchen; Wang, Zijian; Zhao, Chao; Yang, Liang (Frontiers in Neurology, 2024)
Objective: To explore the prevalence of and risk factors for early postoperative seizures in cases with glioma through meta-analysis.: Case-control studies and cohort studies on the prevalence and risk factors of early postoperative seizures in glioma cases were retrieved from CNKI, Wan Fang, VIP, PubMed, Embase, Cochrane Library and Web of Science databases, and the retrieval deadline was April 1st, 2023. Stata15.0 was applied to treat the data. Results: Eleven studies including 488 patients with early postoperative seizures and 2,051 patients without early postoperative seizures. These results suggest that the prevalence of glioma complicated by seizures (ES = 19%, 95% confidence interval [CI] [14%-25%]). The results indicated that: history of seizures (RR = 1.94, 95% CI [1.76, 2.14], P = 0.001), preoperative dyskinesia(RR = 3.13, 95% CI [1.20, 8.15], P = 0.02), frontal lobe tumor (RR = 1.45, 95% CI [1.16, 1.83], P = 0.001), pathological grade ≤2 (RR = 1.74, 95% CI [1.13, 2.67], P = 0.012), tumor≥ 3 cm (RR = 1.70, 95% CI [1.18, 2.45], P = 0.005), tumor resection (RR = 1.60, 95% CI [1.36, 1.88], P = 0.001), tumor edema ≥ 2 cm (RR = 1.77, 95% CI [1.40, 2.25], P = 0.001), and glioma cavity hemorrhage (RR=3.15, 95% CI [1.85, 5.37], P = 0.001). The multivariate analysis resultsshowed: history of seizures, dyskinesia, tumor ≥3 cm, peritumoral edema ≥2 cm and glioma cavity hemorrhage were risk factors for glioma complicated with early postoperative seizures.Significance: Under the existing evidence, seizures history, dyskinesia, frontal lobe tumor, pathological grade ≤2, tumor ≥3 cm, partial tumor resection, edema around tumor ≥2 cm, and glioma cavity hemorrhage are risk factors for glioma complicated with early postoperative seizures.